Esophagojejunostomy Feeding Tube Placement in 5 Dogs with Pancreatitis and Anorexia - Forrest Cummings; Catherine A. Daley (Veterinary Medicine International)
Enteral feeding tube placement has been described in veterinary medicine for several years. Indications include oral, esophageal, gastrointestinal, pancreatic, hepatic, and neurologic diseases. In this paper, endoscopically assisted placement of an esophagojejunostomy (EJ) feeding tube in dogs with pancreatitis and prolonged anorexia is described. To the author’s knowledge there are no published reports of this procedure. Esophagojejunostomy feeding tubes provide an alternative to other forms of postgastric feeding tube placement (e.g., nasojejunal, gastrojejunostomy, and jejunostomy tubes) without the associated complications of patient discomfort, sneezing, epistaxis, and peritonitis. Tube occlusion, transient vomiting and loose stool were the most commonly reported complications.